Proteomic approaches to unravel the complexity of schizophrenia. (February 2012) - Martins-de-Souza, Daniel; Guest, Paul C; Rahmoune, Hassan; Bahn, Sabine
Schizophrenia is a debilitating mental disorder that affects approximately 30 million people worldwide. The development and progression of this disease is now thought to be precipitated through a complex interaction between altered gene function and environmental factors. Proteomic analyses have been applied extensively over the past 10 years in studies of several tissues from schizophrenic patients, resulting in increased insight into the affected molecular pathways. In addition, these proteomic approaches have led to the identification of a set of molecular biomarker assays as the first blood-based test to aid in the diagnosis of schizophrenia. Here, we discuss the main outcome of these investigations and suggest a practical means of integrating and translating the findings between the brain and peripheral blood to increase our understanding of schizophrenia pathophysiology.